P70 Can antiviral therapy for hepatitis C reduce the prevalence of HCV among injecting drug user populations? A modelling analysis of its prevention utility. (16th November 2010) - Hickman, M; Martin, N; Vickerman, P; Hutchinson, S; Goldberg, D; Foster, G
Abstract : Introduction: HCV antiviral treatment (peginterferon and ribavirin) is effective for individual patients, but few active injecting drug users (IDUs) are treated. Aim: We considered the utility of antiviral treatment for reducing HCV transmission amongst active IDUs. Method: An HCV transmission model amongst IDUs was developed, incorporating HCV antiviral treatment. We projected the chronic prevalence reductions resulting from different treatment rates over 5–40 years. Treatment efficacy was varied for three genotype scenarios (mixed, genotype 1, and genotype 2/3) and assumed to result in IDUs becoming susceptible (75%) or resistant/immune (25%). Two models were considered with treatment non-responders either allowed (unrestricted model) or not allowed (restricted model) to be retreated with the same success rates. Results: In the unrestricted model with mixed genotype, annually treating 10 infections per 1000 IDUs results in a relative decrease in HCV prevalence over 10 years of 31%, 14% or 7% for baseline (untreated endemic chronic infection) prevalences of 20%, 40% or 60%, respectively. Prevalence reductions are lower (by ∼25% at this treatment level) for populations with all genotype 1 and similarly higher for genotype 2/3 populations. Reduction of prevalence to negligible levels within 20 years could be achieved by treating 21 infections per 1000 IDUs annually with 20% baseline prevalence, increasing to 53 or 99 in the 40% and 60% prevalence situation. Restricting retreatment does not alter the short-term (<5 year) projections with low treatment (<20 per 1000 IDUs annually), but reducing prevalence to negligible levels takes longer and becomes impossible at high prevalences (>55%). Lastly, the HCV free life years gained from treating active IDUs are projected to be higher than from treating non-IDUs for prevalences below 60%. Conclusion: Despite the possibility of re-infection, modest rates of HCV treatment amongst active IDUs could effectively reduce transmission. Evaluating and extending strategies to treat HCV among active injectors is warranted.